Negative impact of papillary histological subtype in patients with renal cell carcinoma extending into the inferior vena cava: Single‐center experience. (20th February 2013) - Kondo, Tsunenori; Ikezawa, Eri; Takagi, Toshio; Kobayashi, Hirohito; Hashimoto, Yasunobu; Iizuka, Junpei; Omae, Kenji; Yoshida, Kazuhiko; Tanabe, Kazunari
Abstract : Objectives: To investigate the impact of histological subtypes on the survival of patients presenting with renal cell carcinoma extending into the inferior vena cava. Methods: From January 1985 until October 2011, 68 patients with renal cell carcinoma extending into the inferior vena cava underwent radical nephrectomy and inferior vena cava thrombectomy at Tokyo Women's Medical University, Tokyo, Japan. Their clinical and pathological parameters were reviewed from the medical charts. Results: The median follow up was 19 months (range 0.1–144 months). The tumor thrombus level was I in four patients (6%), II in 38 patients (56%), III in 12 patients (18%) and IV in 14 patients (20%). Papillary histological subtype was found in seven patients (10%), and clear cell in 61 patients (90%). Patients with a papillary subtype had a significantly worse survival outcome than the patients with the clear cell subtype (median survival time 9.0 vs 36.1 months, P  < 0.001). Multivariate analysis also showed that the papillary subtype was the only independent prognostic factor for unfavorable cancer‐specific survival ( P  = 0.03). When the patients presented with metastases to lymph nodes or distant metastases, the median survival of the patients with a papillary subtype was extremely short, at just 5.2 months compared with those with a clear cell subtype (24.0 months, P  = 0.001). Conclusions: Patients with renal cell carcinoma extending into the inferior vena cava with a papillary subtype show a considerably shorter survival compared with those with a clear cell subtype. The papillary renal cell carcinoma extending into the inferior vena cava patient might be an inappropriate candidate for extensive surgery when metastases to nodes or distant organs are found.